Book Reviews. - Batoff, Mitchell E. (Science Education)
The article reviews the books on science education including "Something of Value: A Summary of Findings and Recommendations for Improving Elementary Science in Massachusetts," "Essentially Elementary Science: A Report on the Status of Elementary Science in Massachusetts Schools," and "Lively Elementary Science Programs: A Handbook of Suggestions for Introducing and Maintaining Innovative Science Activities."